Bloom of Gymnodinium catenatum in Bahía Santiago and Bahía Manzanillo, Colima, Mexico - Quijano-Scheggia, Sonia; Olivos-Ortiz, Aramis; Bustillos-Guzmán, José J.; Garcés, Esther; Gaviño-Rodríguez, Juan H.; Galicia-Pérez, Marco A.; Patiño-Barragan, Manuel; Band-Schmidt, Christine J.; Hernández-Sandoval, Francisco J.; López-Cortés, David J. (Revista de Biología Tropical, 2012)
Gymnodinium bloom events are of concern, since they produce toxins, which have unfavorable consequences to marine ecosystems, human health and the economy. This report describes the physico-chemical conditions that were present during the algal bloom event on May 2010 in Bahía Manzanillo and Bahía Santiago, Colima, Mexico. For this, seawater nutrient analysis, phytoplankton counts, identification, and toxicity tests were undertaken. Nutrients in seawater were determined using colorimetric techniques, the higher concentrations (8.88μM DIN, 0.78μM PO4 and 24.34μM SiO2) were related with upwelling waters that promoted the algal bloom that began after registering the year lowest sea-surface temperature, favoring the rapid growth of G. catenatum (up to 1.02 x107cells/L). Phytoplankton counting was carried out using sedimentation chambers and cells enumerated on appropriated area. The bloom persisted in the bays for approximately two weeks and was associated with toxicity (determined with HPLC) in local oysters (1525.8μg STXeq/100g), and in phytoplankton (10.9pg STXeq/cells) samples. Strong variations in cell toxicity (1.4 to 10.9pg STXeq/cells), most likely reflected the availability of inorganic nutrients. The toxin profile of the phytoplankton samples consisted of 11 toxins and resembled those recorded for several strains of G. catenatum isolated from other coastal areas of Mexico.